Analysis of Albumin to Globulin Ratio as A Prognostic Predictor in Lupus Nephritis Patients - St. Sandra Karyati Serel; Yuyun Widaningsih; Fitriani Mangarengi (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2024)
Lupus Nephritis (LN) is a manifestation of Systemic Lupus Erythematosus (SLE), which targets the kidney. Based on histopathology, the World Health Organization divides the disease into five classes: normal pattern, mesangial, focal, diffuse proliferative, and membranous. Albumin to Globulin Ratio (AGR) compares serum albumin with serum globulin levels. Low AGR value is associated with poor prognosis of diseases such as cancer, liver cirrhosis, and other chronic inflammatory diseases such as LN. This study aimed to analyze the AGR value as a prognostic predictor in LN patients based on disease classes with a retrospective descriptive cross-sectional approach. Total subjects were 109, which consisted of class 1 (n=15), class 2 (n=37), class 3 (n=9), class 4 (n=21), and class 5 LN (n=27). Data of disease classes, serum albumin, and serum globulin/total protein levels were collected. SPSS version 25, Mann-Whitney, Kruskal-Wallis, Chi-Square, and Spearman's correlation test were used for statistical analysis. The ROC curve determined the cut-off. Test results were significant if p <0.05. The lowest mean AGR value (0.79) was found in class 4 LN (p<0.05). The optimal cut-off AGR was 1.10 to categorize mild-moderate and severe degrees. AGR prognostic value: sensitivity=95.8%; specificity=78.8%; Positive Prediction Value (PPV)=78.0%; Negative Prediction Value (NPV)=96.0%, accuracy = 86.2%. There was a negative strong correlation between the AGR value and LN class with a correlation coefficient R of -0.777 (p<0.001). AGR marker has a good sensitivity and specificity as a predictor of LN progression.